Berek & Novak's gynecology. - Berek, Jonathan S.; Novak, Emil, 1883-1957. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"Berek and Novak's Gynecology is the gold standard text in general gynecology serving both as a comprehensive reference and a practical, clinically-oriented text. This reference is not only a must-have product for residents in training, but it offers information for the practicing physician. The book covers the entire spectrum of women's healthcare by offering guidance for the management of specific gynecologic conditions in eight sections. The first two sections cover principles of practice and initial assessment and the relevant basic science. The third section is on preventive and primary care for women, and the remaining five sections are directed at methods of diagnosis and management in general gynecology, operative general gynecology, urogynecology and pelvic reconstructive surgery, reproductive endocrinology, and gynecologic oncology"--Provided by publisher.